Rules of summer - Tan, Shaun; Arthur A. Levine Books (New York, NY : Arthur A. Levine Books, an imprint of Scholastic Inc., 2014)
Two boys explain the occasionally mysterious "rules" they learned over the summer, like never eat the last olive at a party, never ruin a perfect plan, and never give your keys to a stranger.
Keywords: Friendship -- Juvenile fiction; Summer -- Juvenile fiction; Conduct of life -- Juvenile fiction; Friendship -- Fiction; Summer -- Fiction; Conduct of life -- Fiction